Microglia-specific NF-κB signaling is a critical regulator of prion-induced glial inflammation and neuronal loss. - Arielle J D Hay; Katriana A Popichak; Genova Mumford; Jifeng Bian; Payton Shirley; Lauren Wolfrath; Michael Eggers; Eric M Nicholson; Ronald B Tjalkens; Mark D Zabel; Julie A Moreno (PLoS Pathogens, 2025)
Prion diseases are a group of rare and fatal neurodegenerative diseases caused by the cellular prion protein, PrPC, misfolding into the infectious form, PrPSc, which forms aggregates in the brain. This leads to activation of glial cells, neuroinflammation, and irreversible neuronal loss, however, the role of glial cells in prion disease pathogenesis and neurotoxicity is poorly understood. Microglia can phagocytose PrPSc, leading to the release of inflammatory signaling molecules, which subsequently induce astrocyte reactivity. Animal models show highly upregulated inflammatory molecules that are a product of the Nuclear Factor-kappa B (NF-κB) signaling pathway, suggesting that this is a key regulator of inflammation in the prion-infected brain. The activation of the IκB kinase complex (IKK) by cellular stress signals is critical for NF-κB-induced transcription of a variety of genes, including pro-inflammatory cytokines and chemokines, and regulators of protein homeostasis and cell survival. However, the contribution of microglial IKK and NF-κB signaling in the prion-infected brain has not been evaluated. Here, we characterize a primary mixed glial cell model containing wild-type (WT) astrocytes and IKK knock-out (KO) microglia. These cultures show a near ablation of microglia compared to WT mixed glial cultures, highlighting the role of IKK in microglial survival and proliferation. We show that, when exposed to prion-infected brain homogenates, NF-κB-associated genes are significantly downregulated, but prion accumulation is significantly increased, in mixed glial cultures containing minimal microglia. Mice with IKK KO microglia show rapid disease progression when intracranially infected with prions, characterized by an increased density of activated microglia and reactive astrocytes, development of spongiosis, and accelerated loss of hippocampal neurons and associated behavioral deficits. These animals display clinical signs of prion disease early and have a 22% shorter life expectancy compared to infected wild-type mice. Intriguingly, PrPSc accumulation was significantly lower in the brains of terminal animals with IKK KO microglia compared to terminal WT mice, suggesting that accelerated disease is independent of PrPSc accumulation, highlighting a glial-specific pathology. Together, these findings present a critical role for microglial IKK and NF-κB signaling in host protection against prion disease.